2003
DOI: 10.1001/jama.290.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tifacogin (Recombinant Tissue Factor Pathway Inhibitor) in Severe Sepsis

Abstract: YSTEMIC ACTIVATION OF COAGUlation and thrombus formation in the microvasculature accompanies organ dysfunction and excess mortality in severe sepsis. 1 Tissue factor (thromboplastin) is a major initiator of the blood coagulation process. 2 Tissue factor is a transmembrane cell surface receptor for plasma clotting factor VII and exhibits homol-Author Affiliations, Financial Disclosure, and the OPTIMIST Study Group are listed at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
483
0
24

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 900 publications
(514 citation statements)
references
References 19 publications
7
483
0
24
Order By: Relevance
“…Based on the studies presented here, release of polyP by infectious microorganisms could have potent procoagulant and antifibrinolytic effects, enhancing the host defense role of the blood clotting and fibrinolytic systems. In addition, the ability of polyP released by activated platelets and͞or bacteria to severely abrogate TFPI function might limit the effectiveness of TFPI as a drug (Tifacogin) in combating disseminated intravascular coagulation in sepsis (24). Instability of polyP in plasma and serum.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the studies presented here, release of polyP by infectious microorganisms could have potent procoagulant and antifibrinolytic effects, enhancing the host defense role of the blood clotting and fibrinolytic systems. In addition, the ability of polyP released by activated platelets and͞or bacteria to severely abrogate TFPI function might limit the effectiveness of TFPI as a drug (Tifacogin) in combating disseminated intravascular coagulation in sepsis (24). Instability of polyP in plasma and serum.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few decades, although some anticoagulant agents, such as antithrombin (AT), tissue factor pathway inhibitor, and activated protein C, have been investigated for use in patients by international large randomized controlled trials (RCTs), no remarkable effect on the mortality rate has been reported 4, 5, 6, 7. However, the post‐hoc subgroup analyses of those RCTs indicated that the anticoagulant therapies resulted in improved mortality rates in patients with sepsis‐induced DIC 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Although the DIC subcommittee of the Scientific Standardized Committee (SSC) in the ISTH emphasized vascular endothelial cell injury as a definition of DIC [3], scoring system based on these three diagnostic criteria do not reflect vascular endothelial cell injury. Recent clinical trials for severe sepsis [5][6][7] showed that the mortality rate of patients with severe sepsis was 35-45% and was even higher in patients with DIC than patients without DIC. The frequency of DIC in patients with severe sepsis was 40.7% according to the KyberSept trial results (antithrombin; AT) [5] and 22.4% in the PROWESS study (recombinant activated protein C; APC) [6].…”
Section: Introductionmentioning
confidence: 99%